2020
DOI: 10.3168/jds.2019-17033
|View full text |Cite
|
Sign up to set email alerts
|

Effects of wheat straw chop length in high-straw dry cow diets on intake, health, and performance of dairy cows across the transition period

Abstract: The study investigated the effect of chop length of wheat straw in a high-straw dry cow diet on the feeding behavior, health, and performance of Holstein dairy cows across the transition period. Forty cows were enrolled at dry off, approximately 45 d before expected calving, and assigned to 1 of 2 dietary treatments containing (on a dry matter basis) 36% corn silage, 35% dry cow pellet, and 29% wheat straw. Diets were formulated to target an energy consumption of 19 Mcal/d of net energy for lactation per cow. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 59 publications
1
19
0
Order By: Relevance
“…Contrary to our hypothesis, and in agreement with Havekes et al (2020), dietary treatment in the dry period did not influence how cows sorted their diet postcalving. Sorting during early lactation, when energy demands are high, is likely more related to energy balance (DeVries et al, 2011;Moore and DeVries, 2018) than it is related to a carry-over effect from the dry period.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…Contrary to our hypothesis, and in agreement with Havekes et al (2020), dietary treatment in the dry period did not influence how cows sorted their diet postcalving. Sorting during early lactation, when energy demands are high, is likely more related to energy balance (DeVries et al, 2011;Moore and DeVries, 2018) than it is related to a carry-over effect from the dry period.…”
Section: Discussionsupporting
confidence: 70%
“…Interestingly, cows sorted against the fine fraction, which was surprising as these are usually sought-after particles (Miller-Cushon and DeVries, 2017). Similar sorting results were seen when dairy cows were fed finely chopped straw in both a lactating ration (Coon et al, 2018) and a dry cow ration (Havekes et al, 2020), suggesting that cows may prefer not to consume straw fines, which would have made up a large proportion of the fine particle fraction.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Havekes et al [32][33][34] very recently proposed a variety of strategies to reduce the sorting behavior in low energy diets in the dry period. In a first experiment [32], they demonstrated that prepartum cows being fed a short chop length (2.54 cm screen) of wheat straw is preferable since it was associated with lower serum BHB concentration in the third week postpartum compared to that in cows fed a long chop length (10.16 cm screen) of wheat straw. Although a shorter chop length of straw reduced sorting, it did not (completely) eliminate this behavior.…”
Section: Feeding Controlled-energy and Negative Dietary Cation-anion mentioning
confidence: 99%